Inclusive Technologies and Learning: Research, Practice and Policy - Passey, Don (Social Inclusion, 2015)
This special issue focuses on an important contemporary concern—inclusive technologies and learning. Since the 1960s there has been a continued development and diversification of digital technologies used across societal sectors (Bijker, Hughes, Pinch, & Douglas, 2012), enabling applications not solely within business and commerce, but significantly within educational and social settings (such as those discussed by The Metiri Group, 2006, for example), supporting communication and learning (for example, shown by Richardson, 2012), providing opportunities to widen and deepen reach and interactions (as indicated, for example, by Kim, Hagashi, Carillo, Gonzales, Makany, Lee, & Gàrate, 2011). It can be argued that such developments have created many divisions and challenges too (Resta, & Laferrière, 2008); individuals as well as nations may not have the same access or facilities as others (ITU, 2015); and issues such as exploitation and exclusion are regularly highlighted (Dutta, Geiger, & Lanvin, 2015). This special issue is concerned with inclusive technologies and learning, related to social inclusion.